In Situ and Operando Characterization Techniques in Stability Study of Perovskite-Based Devices - Bingchen He; Chenyue Wang; Jielei Li; Zhenhuang Su; Guichuan Xing; Xingyu Gao; Shi Chen (Nanomaterials, 2023)
Metal halide perovskite materials have demonstrated significant potential in various optoelectronic applications, such as photovoltaics, light emitting diodes, photodetectors, and lasers. However, the stability issues of perovskite materials continue to impede their widespread use. Many studies have attempted to understand the complex degradation mechanism and dynamics of these materials. Among them, in situ and/or operando approaches have provided remarkable insights into the degradation process by enabling precise control of degradation parameters and real-time monitoring. In this review, we focus on these studies utilizing in situ and operando approaches and demonstrate how these techniques have contributed to reveal degradation details, including structural, compositional, morphological, and other changes. We explore why these two approaches are necessary in the study of perovskite degradation and how they can be achieved by upgrading the corresponding ex situ techniques. With recent stability improvements of halide perovskite using various methods (compositional engineering, surface engineering, and structural engineering), the degradation of halide perovskite materials is greatly retarded. However, these improvements may turn into new challenges during the investigation into the retarded degradation process. Therefore, we also highlight the importance of enhancing the sensitivity and probing range of current in situ and operando approaches to address this issue. Finally, we identify the challenges and future directions of in situ and operando approaches in the stability research of halide perovskites. We believe that the advancement of in situ and operando techniques will be crucial in supporting the journey toward enhanced perovskite stability.